Relationship between the educational qualifications of physics teachers and the achievement of their students - Vallente, Crescencia Lopez 1949- (1976)
The purpose of the study was to determine the relationships between the science/mathematics educational qualifications of physics teachers in the Division of Ilocos Norte and the achievements of their students in Physics and in the NCEE-Science Proficiency Subtest for the school year 1974-1975. Chi square test was employed in the study. The study revealed that only physics, mathematics and other allied science units of physics teachers have significant relations to students' grades in physics. In the case of other student variable, students' raw scores in the NCEE-S, only mathematics, and other Allied Science units of teachers showed significant relationships with students' scores in the NCEE-Science Proficiency Subtest. Physics units, chemistry units and general science units showed no significant relations to students' scores in the NCEE-S.
Vita.
Thesis (M.A. Physics Education)--University of the Philippines, Diliman.
Keywords: Physics teachers -- Philippines -- Ilocos Norte; Physics -- Study and teaching -- Philippines -- Ilocos Norte -- Ability testing; Academic achievement -- Philippines -- Ilocos Norte